Use of autobilevel ventilation in patients with obstructive sleep apnea: An observational study. (12th March 2018) - Baiamonte, Pierpaolo; Mazzuca, Emilia; Gruttad'Auria, Claudia I.; Castrogiovanni, Alessandra; Marino, Claudia; Lo Nardo, Davide; Basile, Marco; Algeri, Margherita; Battaglia, Salvatore; Marrone, Oreste; Gagliardo, Andrea; Bonsignore, Maria R.
Summary: Continuous positive airway pressure (CPAP) is the first‐choice treatment for obstructive sleep‐disordered breathing. Automatic bilevel ventilation can be used to treat obstructive sleep‐disordered breathing when CPAP is ineffective, but clinical experience is still limited. To assess the outcome of titration with CPAP and automatic bilevel ventilation, the charts of 356 outpatients (obstructive sleep apnea, n  = 242; chronic obstructive pulmonary disease + obstructive sleep apnea overlap, n  = 80; obesity hypoventilation syndrome [OHS], n  = 34; 103 females) treated for obstructive sleep‐disordered breathing from January 2014 to April 2017 were reviewed. Positive airway pressure titration was considered successful in the case of sleep‐disordered breathing resolution (apnea–hypopnea index <10/hr) with cumulative time at SaO2  < 90% (CT90%) <10% and/or improved daytime arterial blood gases at the end of titration. CPAP was effective in 268 patients (75.0%). CPAP treatment failure ( n  = 88) occurred in 13.6% of obstructive sleep apnea, 32.5% of overlap, and 85.3% of OHS patients. Compared with successful CPAP cases, patients undergoing the automatic bilevel ventilation trial showed higher body mass index (39.3 ± 10.5 kg/m 2 versus 34.8 ± 6.9 kg/m 2, p  < 0.0001), worse mean nocturnal SaO2 (89.2 ± 4.0% versus 91.3 ± 4.0%, p  < 0.003) and CT90% (40.6 ± 28.6% versus 24.0 ± 23.3%), but similar age (62.8 ± 11.9 years versus 60.5 ± 12.0 years, p  = 0.11), apnea–hypopnea index (39.4 ± 23.2/hr versus 41.0 ± 21.2/hr, p  = 0.55) and oxygen desaturation index (37.8 ± 23.5/hr versus 39.2 ± 21.1/hr, p  = 0.61) at diagnosis. Automatic bilevel ventilation was successful in 79.5% of CPAP treatment failures ( n  = 70). Automatic bilevel ventilation failure was independently associated with baseline body mass index >40 kg/m 2 (odds ratio 6.16, confidence interval 1.50–25.17, p  = 0.011) and CT90% >42% (odds ratio 5.87, confidence interval 1.39–24.83, p  = 0.016). During follow‐up, automatic bilevel ventilation treatment failed in seven patients (10%), and compliance was similar in CPAP (4.5 ± 2.2 hr) and automatic bilevel ventilation (5.2 ± 2.3 hr, p  = 0.09) groups. Automatic bilevel ventilation was useful to treat sleep‐disordered breathing, but failed in patients with severe OHS.